2004
DOI: 10.1109/tasc.2004.831054
|View full text |Cite
|
Sign up to set email alerts
|

Performances of a Linear Type Magnetic Flux Pump for Compensating a Little Decremented Persistent Current of HTS Magnets

Abstract: This paper describes the characteristics of a linear type magnetic flux pump recently developed. The linear type flux pump has been fabricated to apply to compensate decremented persistent current of HTS applications such as NMR and MRI system. The linear type magnetic flux pump mainly consists of 3-phase AC armature coil, DC bias coil and superconducting Nb foil. In the preliminary experiment, the flux pump can charge the pumping-up current in the load coil of 1.3 mH during 1000 seconds under the DC bias curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Topological generators received new impetus as precision direct current sources in connection with the development of MRIs based on HTSC [7][8][9][10].…”
Section: Topological Generators With Phase Rss Of Htscmentioning
confidence: 99%
“…Topological generators received new impetus as precision direct current sources in connection with the development of MRIs based on HTSC [7][8][9][10].…”
Section: Topological Generators With Phase Rss Of Htscmentioning
confidence: 99%
“…The operating characteristics of LTMFP have already been investigated under various conditions. Moreover, it has been observed that the current pumping of the LTMFP can be controlled by frequency of the 3-phase inverter [5], [6].…”
Section: Introductionmentioning
confidence: 99%